Investigating the Mechanism of Shengmaiyin (Codonopsis pilosula) in the Treatment of Heart Failure Based on Network Pharmacology - Kan, Mo; Wang, Jifeng; Ming, Sitong; Sui, Xin; Zhang, Zhuang; Yang, Qing; Liu, Xiaoran; Lin, Jianan; Zhang, Yanhong; Pang, Qihang; Liu, Yaxin; Li, Zhen; et al. (Combinatorial Chemistry & High Throughput Screening, 2022)
Background and Objective: To explore the molecular mechanism by which Shengmaiyin (Codonopsis pilosula) (SMY) improves isoproterenol (ISO)-induced heart failure (HF) in rats via a traditional Chinese medicine (TCM) integrated pharmacology research platform, The Chinese Medicine Integrated Pharmacology Platform (TCMIP V2.0). Method: The chemical constituents and drug targets of SMY medicines were identified through TCMIP, and HF disease target information was collected. A prescription Chinese medicinecomponent- core target network was constructed through the TCM network mining module, and biological process and pathway enrichment analyses of core targets were conducted. In vivo experiments in rats were performed to verify the pathway targets. Hematoxylin and eosin staining was used to observe myocardial tissue morphology. ELISA kits were used to detect cAMP content, and Western blotting was used to detect the expression levels of signaling pathway-related proteins. Results: The TCMIP analysis indicated that SMY treatment of HF activates the GS-β-adrenergic receptor (βAR)-cAMP-protein kinase A (PKA) signaling pathway. The in vivo experimental results confirmed this finding. High-dose SMY significantly improved the morphology of ISO-injured myocardium. The levels of G-protein-coupled receptor (GPCR), adenylate cyclase (AC), βAR, and PKA proteins in myocardial tissue were significantly increased in the SMY group. In addition, the content of cAMP in myocardial tissue was increased, and the content of cAMP in serum was decreased. Conclusion: Based on the analysis of TCMIP, SMY treatment of HF may activate the GS-βARcAMP- PKA signaling pathway. The findings provide a theoretical basis for further research on the anti-HF mechanism of SMY.
Keywords: TCMIP V2.0